Cardiac Autonomic Dysfunction in Patients with Schizophrenia and Their Healthy Relatives – A Small Review - Bär, Karl-Jürgen (Frontiers in Neurology, 2015)
The majority of excess mortality among people with schizophrenia seems to be caused by cardiovascular complications, and in particular, coronary heart disease. In addition, the prevalence of heart failure and arrhythmias is increased in this population. Reduced efferent vagal activity, which has been consistently described in these patients and their healthy first-degree relatives, might be one important mechanism contributing to their increased cardiac mortality. A decrease in heart rate variability (HRV) and complexity was often shown in unmedicated patients when compared to healthy controls. In addition, faster breathing rates, accompanied by shallow breathing, seem to influence autonomic cardiac functioning in acute unmedicated patients substantially. Moreover, low physical fitness is a further and independent cardiac risk factor present in this patient population. Interestingly, new studies describe chronotropic incompetence during physical exercise as an important additional risk factor in patients with schizophrenia. Some studies report a correlation of the autonomic imbalance with the degree of positive symptoms (i.e. delusions) and some with the duration of disease. The main body of psychiatric research is focused on mental aspects of the disease, thereby neglecting obvious physical health needs of these patients. Here, a joint effort is needed to design interventional strategies in everyday clinical settings to improve physical health and quality of life.